A Study of Awareness on Artificial Insemination among Medical College Students - Shifa Shahina Nijamudeen1 , Dekal V2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Artificial Insemination (AI) is the deliberate introduction of sperm into a female’s cervix or uterine cavity for the purpose of achieving a pregnancy through in vivo fertilization by means other than sexual intercourse. This is one among the methods of assisted reproductive technique. This study aims to find out the level of awareness about Artificial Insemination among medical students Materials and Method: This is a questionnaire-based study. A self-administered questionnaire in multiple choice format distributed among the medical students of Saveetha medical college. Total of 120 students, Forty students from each batch from second to final year were randomly chosen to participate in the the survey. Results: 120 medical students participated in the survey out of which 76.67% of students had adequate awareness on artificial insemination. 85% of students knew the correct definition of AI while 86.74% were able to correctly identify the techniques used for artificial insemination. Final years medical students had more awareness on artificial insemination than their junior colleagues, and 2nd years medical students had least awareness.Students have inadequate knowledge on the technical aspect of artifical insemination like storage of semen (21%, n-25) and the time duration of sperm viability (54%, n-65) etc. Students also having inadequate knowledge on the legal, social and psychological issues like donor selection, consent of the spouse and the importance of understanding between the partners on artificial insemination. Discussion: Most of the respondents knew about the basics of Artificial insemination with less awareness on its technical aspect, legal and ethical implications. Medical education have been a good source of information and the inclusion of Artificial Insemination as a form of infertility management in the curriculum of medical students could help in increasing awareness among students.